One-dimensional coordination polymers of [Co3(dpa)4]2+ and [MF6]2− (M = ReIV, ZrIV and SnIV). Issue 100 (22nd October 2015) - Bulicanu, Vladimir; Pedersen, Kasper S.; Rouzières, Mathieu; Bendix, Jesper; Dechambenoit, Pierre; Clérac, Rodolphe; Hillard, Elizabeth A.
Abstract : 1-D coordination polymers of alternating metal–metal bonded trinuclear [Co3 (dpa)4 ] 2+ building blocks and [MF6 ] 2− (M = Re, Zr, Sn) linkers have been structurally and magnetically characterized. Abstract : One-dimensional coordination polymers of alternating metal–metal bonded trinuclear [Co3 (dpa)4 ] 2+ (dpa = the anion of 2, 2′-dipyridylamine) building blocks and [ReF6 ] 2− (1 ), [ZrF6 ] 2− (2 ) or [SnF6 ] 2− (3 ) linkers have been self-assembled and crystallographically characterized. Magnetic measurements reveal a significant ferromagnetic coupling ( J / k B = +9.9 K) between S = 1/2 Co3 6+ and S = 3/2 Re IV magnetic sites through a single, unsupported fluoride bridge in1 .